Acevedoa nom. nov., a replacement name for andersonia Arce & Lutz 2010 (insertae sedis), preoccupied by andersonia R.Br. 1810 (plantae, magnoliophyta, ericaceae) - Arce, Federico Exequiel (2014)
Andersonia Arce & Lutz, adopted name for a fructification genus, is an illegitimate homonym, therefore the following replacement name is proposed: Acevedoa nom. nov. for Andersonia Arce & Lutz (non R. Br. 1810 nec Willd. ex Roem. and Schult. 1819, nom. Illeg. nec Roxb 1832, nom. Illeg.). The name Andersonia was first validly published by R. Brown for a genus of flowering plants included in the family Ericaceae. Moreover, Acevedoa rastroensis comb. nov. is proposed.